Individual Relationship Analysis: A Phenomenon of Using Instagram Second Account - Della Giska Meidiani; Maulina Larasati Putri; Vera Wijayanti Sutjipto (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The rapid advancement of technology has significantly transformed the way individuals communicate, particularly through social media platforms. These platforms, often referred to as part of cyberspace, have facilitated seamless and widespread interpersonal interaction. Social media has become a space where various forms of social activity are displayed, including the phenomenon of self-presentation or "showing off. This study employs Social Penetration Theory, which elucidates the process through which interpersonal relationships evolve from superficial exchanges to deeper, more intimate levels of communication. Central to this theory is the concept of self-disclosure, which is considered a driving force in the development of personal relationships. A qualitative research methodology was adopted, utilizing a descriptive phenomenological approach to explore lived experiences and the subjective meanings behind them. Data were collected through a combination of observations, in-depth interviews, and documentation. The findings reveal that the progression of relational depth among individuals on social media is significantly influenced by the degree of self-disclosure. One notable phenomenon observed is the use of secondary Instagram accounts (often referred to as "second accounts" or "finstas"), which serve as private spaces where users feel more comfortable engaging in authentic self-expression and disclosure.